(untitled) (Unilorin Journal of Lifelong Education, 2025)
Numerous Internally Displaced Persons (IDPs) confront the loss of their livelihoods due to forced displacement. As a response, both state and non-state actors provide vocational training to empower IDPs, fostering self-reliance and independence. Specifically, the study: (i) finds out the attitudes of the IDPs towards the vocational skills training programmes in SouthSouth Nigeria (ii) determines if there is any difference in the attitudes of IDPs towards vocational skill training programmes in IDP camps in South-south Nigeria based on location (iii) determines if there is any difference in the attitudes of male and female IDPs towards vocational skills training programmes in IDP camps in South-south Nigeria. The representativeness of the 398 IDP sample may be limited, self-report bias could affect accuracy, findings may lack generalisability to other regions, and unaccounted external factors might influence attitudes. The descriptive research design of the survey type was adopted for the study. Multi-stage sampling technique was used to select a sample size of 398 IDPs from South-South Nigeria. A researcher-designed questionnaire and a checklist validated by 3 experts from the Department of Vocational and Technical Education, University of Benin, Nigeria, were used for the data collection. A reliability coefficient (r) of 0.73 was obtained through test-retest method. Data collection was conducted by the researcher and three trained research assistants. Descriptive statistics of frequency count, mean and percentage were used to answer the research questions raised, while inferential statistics of t-test was used to analyse the postulated null hypotheses at 0.05 level of significance, using Statistical Package for Social Science (SPSS) version 20.0. The findings showed that: (i) IDPs have positive attitude towards the vocational skills training programmes. (ii) There is no significant difference in the attitude of IDPs towards vocational skills training programmes in IDP camps in South-South Nigeria based on location. (iii) There is significant difference in the attitude of male and female IDPs towards vocational skills training programmes in IDP camps in South-South Nigeria. Based on the findings, the study recommended among others that Government agencies overseeing IDPs should ensure sustained positive attitudes of IDPs by implementing measures like incentives and start-up packs. They should also remove barriers hindering participation in skill programmes and allow free choice of vocational training regardless of gender of IDPs.